Control System Development and Implementation of a CNC Laser Engraver for Environmental Use with Remote Imaging - Attar, Hani; Abu-Jassar, Amer Tahseen; Amer, Ayman; Lyashenko, V.; Yevsieiev, V.; Khosravi, Mohammad R. (Hindawi, 2022)
is article is aimed at studying the features of the control systems development for a small-sized Computer Numerical Control (CNC) portative laser engraver. e CNC is implemented in mobile maintenance and repair platforms for remote sensing of the environment where the wild environment may not allow us to access the animals and places. e proposed work in this paper is based on recent research, which shows that applying the automated CNC speeds up the processes of repair, modernizes the equipment size, and signi cantly reduces the economic costs; accordingly, the authors developed a block diagram of a portable CNC laser engraver. e choice of the hardware was also made, taking into account the possibility of quick replacement in the eld, which reduces the repair time and the cost of the developed layout. A control system based on the selected modules was synthesized, and a stability check was carried out using MatLab tools. To check the correctness of the developed control system, the authors developed and assembled an experimental layout to illustrate the results of engraving on such a layout. Finally, the stability and sensitivity of the proposed system have been obtained and proved that the system works in a comfortable zone of stability. e obtained results show that the proposed CNC laser engraver has achieved the expected improvements (high speed, small size, short production and repairing time, minimum human in uence factor, and achieving a better outcome).
Keywords: Control System; Laser; Remote Imaging; Computer Numerical Contro